Books and prints at the heart of the Catholic Reformation in the Low Countries (16th-17th centuries) - Adam, Renaud; De Marco, Rosa; Walsby, Malcolm (Library of the written word, 2023)
"Often considered as the first phenomenon of mass media in history, the use of books and prints by Protestants has been widely studied and has generated a rich and plentiful bibliography. In contrast, the production and use of these supports by the partisans of the Counter-Reformation have not received the attention they deserve, especially in the context of the Low Countries. The twelve contributors provide new perspectives on the efficacy of the handpress book industry to support the Catholic strategy of the Spanish Low Countries and underlines the mutually beneficial relationship between proponents of the Counter-Reformation and the typographic world. It is therefore also an important contribution to our understanding of sociocultural and socioeconomic background of the Catholic Netherlands"--